ASOSIASI FUNGI MIKORIZA (FMA) ARBUSKULA PADA BEBERAPA TINGKAT UMUR TANAMAN JABON (Anthocephalus cadamba) DI DESA SEMBERANG KECAMATAN SAMBAS KABUPATEN SAMBAS KALIMANTAN BARAT - Qomariah, Ririn; Muin, Abdurrani; AM, Iskandar (JURNAL HUTAN LESTARI, 2017)
Jabon  that is known  as  Anthocephalus cadamba, is one species of species and that has high prospects for industrial tree plantations because growth is very fast and has the ability to adapt onvarious site conditions. Jabon to improve the growth of jabon that can grow succesfully, so this plant need help to be introduced by  biological agents one of which is the arbuscular mycorrhizal fungi. The purpose of this study was to known study 1  The number of spores and genus AMF associated with jabon, level of association that occur between the AMF with jabon age of 1, 1½ and 2years. Research was carried out for 2 months, starting with the taking of 3 samples jabon age of 1, 1½ and 2 years randomized rural in village Semberang districts Sambas Counties Sambas West Kalimantan. Observation of soil and root samples was carried out in the laboratory of Faculty of Forestry Silviculture Uvinersity Tanjungpura. This  method of isolate spores was been trough a gradual process of wet screening on the ground, them it the coloring on the roots and determine the characteristics of the spores to the genus level and calculate the percentage of infected root AMF. The results of this study were found 6 genus Glomus ang 1 genus Gigaspora and the rage percentage of root infection was 60 % (high) – 97 % (very high) included in the classifications of root infection grades 4 and 5. Keyword: association, arbuscular mycorrhizal fungi (AMF), Jabon (Anthocephalus cadamba)